Synthesis and Characterization of Some Organometallic Compounds of Iridium(I) with 2-Mercapto-3-Substituted Quinazoline-4-ones - Pandey, R.N.; Sharma, Manju; Sharma, R.N.; Chandrashekhar, N. (Asian Journal of Chemistry, 2016)
Few organo-iridium complexes with 2-mercapto-3-substituted quinazoline-4-ones have been prepared and characterized by various physico-chemical methods. These are found to be non-hygroscopic, air-stable, non-conducting and diamagnetic in nature. The nature of shifting and change in intensity of all four thioamide bands of ligands are used to diagnose the bonding mode between the ligand and metal. Metal-ligand vibrations in the far infrared spectra of complexes have been thoroughly examined.